2013
DOI: 10.5664/jcsm.3078
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Rapid Eye Movement Sleep Atonia in Patients with REM Sleep Behavioral Disorder, Narcolepsy, and Isolated Loss of REM Atonia

Abstract: Study Objectives: To compare the amounts of REM sleep without atonia (RSWA) between patients with REM sleep behavior disorder (RBD), "isolated loss of REM atonia," narcolepsy, and control subjects and determine if there were threshold values for the amount of RSWA that differentiate each group from controls. Methods: Retrospective analyses of polysomnography (PSG) records were used employing strict quantitative criteria for the measurement of phasic and tonic EMG activity during REM sleep. The PSG recordings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…We suggest that when evaluating subjects in a clinic, the features in combination with a nocturnal SOREMP could be used to screen for type 1 narcolepsy based on the results of a nocturnal PSG alone. Combined with other PSG features as well, such as state-space analysis [43] or analysis of REM sleep atonia [44] in narcolepsy, these features could lead to new diagnostic procedures for type 1 narcolepsy.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that when evaluating subjects in a clinic, the features in combination with a nocturnal SOREMP could be used to screen for type 1 narcolepsy based on the results of a nocturnal PSG alone. Combined with other PSG features as well, such as state-space analysis [43] or analysis of REM sleep atonia [44] in narcolepsy, these features could lead to new diagnostic procedures for type 1 narcolepsy.…”
Section: Discussionmentioning
confidence: 99%
“…As for the scoring methods of RWA proposed by the AASM, no optimal cut-off value for diagnosis of RBD had been reported during the study period. Therefore, we adopted the cut-off value for phasic EMG activity in the submentalis muscle referring to a recent report in which phasic EMG activity in the submentalis muscle was scored in a similar way to the AASM scoring methods[ 32 ]. Third is the possible heterogeneity of the patients diagnosed as IHS w/o LST.…”
Section: Discussionmentioning
confidence: 99%
“…According to the aforementioned scoring rules[ 29 ], board-certified sleep technologists carefully scored RWA on the chin EMG. Referring to the recent study defining cut-off value of RWA to discriminate RBD from controls, subjects having more than 1.22% of a proportion of 3-sec mini epochs with phasic activity to the total duration of REM sleep were defined as those with RWA with allowance of scoring using 3-sec epoch alternative to 2-sec epoch[ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…4 for the distribution of delta power in the course of the night). In recent years, studies on REM sleep behavior disorder showed increased evidence that the loss of REM sleep atonia may be an early manifestation of degenerative neurological disease [42,43]. A simple measure to automatically quantify the time in REM sleep without atonia - the atonia index - was developed and validated by Ferri et al [44] in 2010.…”
Section: Discussionmentioning
confidence: 99%